Bi2O3 quantum dots decorated TiO2 nanobelt heterojunctions with enhanced visible‐light photoactivity. (1st December 2018) - Chen, Zimei; Wang, Jinguo; Zhai, Guangjun; He, Rong; Jia, Xin; Sun, Qiuyan; Men, Yong
Abstract : Bi2 O3 quantum dots decorated TiO2 nanobelt heterojunctions were synthesised by a facile two‐step hydrothermal process. The Bi2 O3 quantum dots highly dispersed on the surface of TiO2 nanobelts resulted in more photosensitising sites and Bi2 O3 –TiO2 heterojunctions, leading to the enhanced absorbance for visible light. The strong Bi2 O3 –TiO2 interaction promoted the rapid transfer of photoelectrons from Bi2 O3 to TiO2 and thus inhibited their recombination with holes. Meanwhile, the high‐surface area facilitated the adsorption and diffusion of reactant molecules. As a result, this photocatalyst exhibited highly enhanced photoactivity in degradation of organic dyes under visible‐light irradiation, which also displayed strong durability owing to the strong Bi2 O3 –TiO2 interaction against the leaching of Bi2 O3 quantum dots.